SIMS investigations of isotope effects at a processed solid surface - Nikitenkov N. N. Nikolai Nikolaevich; Kolokolov D. Yu.; Chernov I. P. Ivan Petrovich; Tyurin Yu. I. Yuri Ivanovich
A review of the latest research and the new experimental data obtained by the authors on changes in the isotope composition in the near-surface layers of solids in ion scattering processes, ion sputtering, the secondary ion emission, ion implantation, electrolytic saturation by hydrogen isotopes, thermo-diffusion from external source, and chemical solution action is presented. In all these processes appreciable changes in natural isotopic composition of the near-surface layers have been registered. These changes take place among the secondary emitted and reflected particles also. Investigations of these effects have been made by the methods of secondary ion mass spectrometry (SIMS) and secondary ion energy-mass spectrometry (SIEMS). The many-isotopic samples of molybdenum, nickel implanted in copper, various titanium modifications, thin film titanium-aluminum systems and some others have been used. The general regularities in the changes in the isotope composition by different processes are found. Possible mechanisms of these processes are discussed.